Challenges of demographic changes and digitalization on eco-innovation and the circular economy: Qualitative insights from companies. (10th April 2023) - Hojnik, Jana; Ruzzier, Mitja; Konečnik Ruzzier, Maja; Sučić, Boris; Soltwisch, Brandon
Abstract: The overuse of natural resources through excessive consumptions has led to environmental problems. As a result, there have been calls for a more sustainable, circular and digital future. Research on the topics of eco-innovations and the circular economy have made significant headways toward identifying sustainable solutions, however, the influence of demographic changes and digitization remain underexplored. Therefore, the current study investigates how demographic changes and digitization effect business practices related to eco-innovations and the circular economy. Semi-structured interviews are conducted with ten companies in Slovenia that actively adopt and develop eco-innovations, and moreover employ the principles of a circular economy. These semi-structured interviews specifically explore the impact of digitalization and demographic changes on eco-innovation and how these impacts enable the development of the circular economy. Results suggest that companies are adjusting their products and services to meet changing demands from demographic trends. Relatedly, digitization has allowed them to create new products and optimize existing ones in more sustainable ways, i.e., having less harmful effects on the environment. Specifically, digitization gave them better control over the eco-innovation process, increasing transparency, control, and manageability of the technological process in a way that reduced energy consumption and lessoned the environmental impact. These results are integrated with the existing literature to identify new insights related to the adoption and implementation of eco-innovations in the circular economy. Highlights: We aim to explore the role of demographic changes and digitalization in companies. We focus on companies with eco-innovations (EI) and/or circular economy (CE). We interviewed ten companies from Slovenia with EI and CE practices. Our study offers important insights how companies address digitalization. Our study offers important insights how companies address demographic changes.